Implementasi Asuhan Pasca Keguguran di Wilayah Kerja Puskesmas Paringin Selatan Kabupaten Balangan - Rizni, Ismeily; Dona, Sismeri; Hestiyana, Nita (Pusat Riset dan Inovasi Nasional, 2024)
The background of this study is still high Maternal Mortality Rate (MMR), MMR is one indicator to see efforts to succeed in maternal health, mortality rates can occur during pregnancy, childbirth and postpartum. Miscarriage during pregnancy and incomprehensive post-miscarriage care is one of the causes of MMR. The purpose of this study was to find out how the implementation of post-miscarriage care in the working area of the South Paringin Health Center, Balangan Regency. This research method is descriptive quantitative, using secondary data derived from medical records, the population of this study is all post-miscarriage mothers from January 2021 to October 2022, the sample in this study uses total sampling techniques where all populations are sampled, namely 37 post-miscarriage mothers. The results showed that post-miscarriage care has not been said to be comprehensive because it still focuses on medical management and is only based on patient complaints.